Fixed Point Theorems for Ćirić-Berinde Type Contractive Multivalued Mappings - Seong-Hoon Cho (Abstract and Applied Analysis)
We give a Ćirić-Berinde type contractive condition for multivalued mappings and analyze the existence of fixed point for these mappings.